International Financial Reporting Standards: a look from bibliometrics. - Cuasquer Arteaga, Larent Tatiana
This paper presents the results of the bibliometric analysis of scientific research related to Inter- national Financial Reporting Standards (IFRS). The study was carried out by taking the existing scientific information in the Scopus and Web of Science databases up to February 2024, the date on which the study was conducted. The analysis was carried out using the Bibliometrix library of the R-Project program and the results made it possible to identify a growth in production since 2001, the relevant authors and the most important journals. It was established that scientific produc- tivity is concentrated in a small group of researchers, and most of the articles are published by a few journals. The main topic studied is the impact and adoption of IFRS and it was found that the United States is one of the countries with the highest production of articles.